Effect of vitamin D on bone mineral density of elderly patients with osteoporosis responding poorly to bisphosphonates - Heckman, George A (BioMed Central, 2002)
BACKGROUND: Bisphosphonates are indicated in the prevention and treatment of osteoporosis. However, bone mineral density (BMD) continues to decline in up to 15% of bisphosphonate users. While randomized trials have evaluated the efficacy of concurrent bisphosphonates and vitamin D, the incremental benefit of vitamin D remains uncertain. METHODS: Using data from the Canadian Database of Osteoporosis and Osteopenia (CANDOO), we performed a 2-year observational cohort study. At baseline, all patients were prescribed a bisphosphonate and counseled on vitamin D supplementation. After one year, patients were divided into two groups based on their response to bisphosphonate treatment. Non-responders were prescribed vitamin D 1000 IU daily. Responders continued to receive counseling on vitamin D. RESULTS: Of 449 patients identified, 159 were non-responders to bisphosphonates. 94% of patients were women. The mean age of the entire cohort was 74.6 years (standard deviation = 5.6 years). In the cohort of non-responders, BMD at the lumbar spine increased 2.19% (p < 0.001) the year after vitamin D was prescribed compared to a decrease of 0.55% (p = 0.36) the year before. In the cohort of responders, lumbar spine BMD improved 1.45% (p = 0.014) the first year and 1.11% (p = 0.60) the second year. The difference between the two groups was statistically significant the first year (p < 0.001) but not the second (p = 0.60). Similar results were observed at the femoral neck but were not statistically significant. CONCLUSION: In elderly patients with osteoporosis not responding to bisphosphonates, vitamin D 1000 IU daily may improve BMD at the lumbar spine.